Perceived value of second-hand clothing in centennials: Analysis of antecedents and effects - Cavazos-Arroyo, Judith (2025)
Consumers are increasingly interested in second-hand clothing. This research analyzes how perceived benefits and risks influence the perceived value of second-hand clothing. In addition, we analyze the impact of perceived value on trust and recommendations to wear second-hand clothing. The empirical application uses structural equation modeling on a sample of 310 centennial consumers of second-hand clothing in Chetumal, Mexico. The results show that perceived benefits positively influence the perceived value of second-hand clothing, whereas perceived risks do not affect perceived value. Perceived value positively influences trust, and trust has a positive impact on consumer recommendations to wear second-hand clothing. The main findings suggest that the benefits perceived by consumers are an antecedent of the perceived value of second-hand clothing.